Studi Analisis Komparatif Prestasi Belajar Siswa Lulusan SMP Negeri dan Siswa Lulusan SMP Swasta Pada Mata Pelajaran Pendidikan Agama Islam Kelas X di SMA Negeri 1 Hamparan Perak - Shifa, Mawaddatus; Arsyad, Junaidi; Ardianti, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The research that has been carried out is entitled Comparative Analysis Study of Learning Achievement of Students Who Graduated from State Junior High Schools and Students Who Graduated from Private Junior High Schools in Class X Islamic Religious Education Subjects at SMA Negeri 1 Hamparan Perak. This research aims to determine the comparison of learning outcomes between students who graduated from State Middle Schools and students who graduated from Private Middle Schools in the class X Islamic Religious Education subject at SMA Negeri 1 Hamparan Perak.The method used by researchers is qualitative research. Data collection techniques in this research are observation, interviews, documentation. The data analysis techniques are data reduction, data presentation and drawing conclusions. Research results have shown that students graduating from State Middle Schools show better learning achievements. This is due to the more consistent and systematic basis of religious education received in State Middle Schools, where students are more accustomed to worship routines such as congregational prayers and the application of religious values in everyday life. Meanwhile, students graduating from private junior high schools need more attention and time to adjust, especially in terms of religious discipline and experience of religious values. However, with the right assistance and various programs that support this difference in achievement, optimal results can be achieved.